33. FOOD SAFETY KNOWLEDGE AND PRACTICES AMONG CONSUMERS IN THAI BINH PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to assess the food safety knowledge and practices among consumers in Thai Binh province in 2023.Subject and method: A cross-sectional study was conducted in 2023 in Thai Binh province, involving 249 subjects aged 15-80 years old who are food consumers, aimed at assessing their knowledge and practices regarding food safety.Results: 89.9% of food consumers understand food safety, with 54.7% at level A and 35.2% at level B. Rural areas show 89.1% understanding (59.7% level A, 29.4% level B), and urban areas have 90.8% (55.4% level A, 35.4% level B). Compliance with practical food safety reaches 98.8%, split as 57% level A and 41.8% level B. Purchases are primarily from roadside stalls or markets (66.2%) and supermarkets or clean food stores (62.6%). However, 7.7% reuse spoiled food for cooking, and 57% are aware of mandatory food labeling for health protection.Conclusion: Consumer knowledge and practices in food safety are highly satisfactory, with 89.9% achieving adequate knowledge and 98.8% demonstrating good practices. Over 50% in both rural and urban areas achieve level A (≥ 80% correct answers). However, only 62.6% of consumers choose food from supermarkets or clean food stores. Despite mandatory health labeling, risky behaviors like using spoiled food and improper storage persist. Enhancing food safety communication is crucial to correct these habits among consumers
Keywords: Food safety, knowledge, practices, consumers, Thai Binh.